1988
DOI: 10.1113/jphysiol.1988.sp017379
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of myoglobin diffusivity in the myoplasm of frog skeletal muscle fibres.

Abstract: SUMMARY1. Experiments were carried out on intact, single skeletal muscle fibres from frog in order to estimate the apparent diffusion constant of myoglobin (denoted DAPP) in the myoplasm of living muscle cells. An optical technique was employed to measure myoglobin concentration along the fibre axis following injection of metmyoglobin (denoted metMb) at a point source. The concentration profiles were fitted by the onedimensional diffusion equation to give estimates of DAPP. The method relied on the fact that m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
25
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 44 publications
5
25
0
Order By: Relevance
“…These values have now been supplanted by the significantly smaller values measured by microinjection and photobleaching experiments in living muscle (Baylor and Pape, 1988;Jurgens et al, 1994Jurgens et al, , 2000Papadopoulos et al, 1995Papadopoulos et al, , 2000Papadopoulos et al, , 2001. The value found in photobleaching experiments (1.2×10 -7 ·cm 2 ·s -1 at 22°C or 2.1×10 -7 ·cm 2 ·s -1 at 37°C) is about one-tenth that in dilute solution …”
Section: Diffusivity Of Myoglobinmentioning
confidence: 83%
“…These values have now been supplanted by the significantly smaller values measured by microinjection and photobleaching experiments in living muscle (Baylor and Pape, 1988;Jurgens et al, 1994Jurgens et al, , 2000Papadopoulos et al, 1995Papadopoulos et al, , 2000Papadopoulos et al, , 2001. The value found in photobleaching experiments (1.2×10 -7 ·cm 2 ·s -1 at 22°C or 2.1×10 -7 ·cm 2 ·s -1 at 37°C) is about one-tenth that in dilute solution …”
Section: Diffusivity Of Myoglobinmentioning
confidence: 83%
“…In addition, it is possible that intracellular convection associated with contraction may enhance intracellular transport (Hochachka, 1999;Suarez et al, 2003). There has been limited experimental testing of this hypothesis, although the D of several proteins was not increased by muscle contraction or passive stretching and shortening (Baylor and Pape, 1988;Papadopoulos et al, 2000). To our knowledge the influence of contraction on the diffusion of small metabolites has not been addressed, and further study in this area is warranted.…”
Section: The Intracellular Environment Of Muscle Has Characteristics mentioning
confidence: 91%
“…The diffusion of Mb in skeletal muscle has been of particular interest because of its role in reversibly binding O 2 and therefore serving as a temporary O 2 store and facilitating O 2 diffusion (reviewed in Wittenberg and Wittenberg, 2003). Several studies have found that D of Mb in muscle fibers is about 1/6 to 1/10 of that in aqueous solution (Baylor and Pape, 1988;Jurgens et al, 1994;Papadopoulos et al, 1995;Papadopoulos et al, 2000;Papadopoulos et al, 2001). Measurements of protein diffusion in skeletal muscle from frog (Maughan and Lord, 1988;Maughan and Godt, 1999) and cultured mammalian fibers (Arrio-Dupont et al, 1997;Arrio-Dupont et al, 2000) yielded D values that were minimally 1/3 lower than that in water, and in many cases much more dramatically reduced.…”
Section: The Intracellular Environment Of Muscle Has Characteristics mentioning
confidence: 99%
“…The first measurement of Mb diffusion in an intact muscle cell was that of Baylor and Pape, who microinjected MetMb into frog muscle fibers and measured spectrophotometrically the MetMb concentration profile along the longitudinal fiber axis at various times (Baylor and Pape, 1988 (Jürgens et al, 1994). The diffusion distances observed by them were 70-500m in the longitudinal direction.…”
Section: Spectrophotometric Determination Of Mb Translational Diffusionmentioning
confidence: 99%